Factor Analysis in Adoption of Agricultural Innovations in Arid Areas of Western Rajasthan - Saha, D K; Malhotra, S P; Krishna, G V.S.R (Annals of Arid Zone, 2016)
The technique of factor analysis was adopted to determine the factors associated with the adoption of agricultural innovations. Altogether 12 attributes were subjected to factor analysis. Out of these four factors, viz., adoption behaviour, economic factor, family structure and occupation, were extracted which accounted for 71% of the total variability. Adoption behaviour or expression of innovativeness accounted for highest variability. Multivariate structure of the innovation decision process is concluded from this study.